Sociology in Teaching and Practice: Research and Development Directions of the Institute of Sociology, 2014–2024 - Łaska-Formejster, Alicja; Kretek-Kamińska, Agnieszka; Matuchniak-Mystkowska, Anna; Konecki, Krzysztof T.; Krzewińska, Aneta; Bunio-Mroczek, Paulina; Kotras, Marcin; Dopierała, Renata; Garncarek, Emilia; Stempień, Jakub Ryszard (Scientific Schools and Research Directions at the Faculty of Economics and Sociology, University of Łódź: The Present and the Future, 2025)
The chapter presents the history and contemporary development of the Institute of Sociology at the Faculty of Economics and Sociology, University of Łódź. The authors discuss its scientific and educational traditions, with special attention to the last ten years.